Facilitating the mission and vision of the Ministry of Higher Education - Shuib, Munir; Abdul Rahman, Shukran (2006)
In the Ninth Malaysia Plan, the Ministry of Higher Education (MOHE) has been allocated over RM18 billion to provide better facilities and promote quality at the various universities and colleges in Malaysia. This sum is significantly higher than that was provided under the Eighth Malaysia Plan.